Developing your own environmental database. - Paulu, Christopher A.; Ozonoff, David M.; Coogan, Patricia (Public Health Reports)
Practical advice on constructing an integrated environmental data system for a state or locality is provided. A number of points should be borne in mind when creating such a system, namely, public access does not equate with ease of access, it is advisable not to start with the goal of comprehensiveness, and flexibility should be incorporated into the system. The features and organizational structure of the Massachusetts Environmental Database are described for the purposes of illustration. The choice of database, either a relational database like the Massachusetts Environmental Database or a Geographic Information Systems database, is also discussed.